Within and between-day differences in adolescents’ objectively-measured physical activity and sedentary behavior - Viciana, Jesús (Array, 2019)
A decline in adolescents’ moderate-to-vigorous physical activity (MVPA) and the increase in their sedentary behavior (SB) have been registered all over the world. In order to increase the MVPA and reduce the SB of adolescents, their day has been analyzed by segments of time, verifying the contribution of each to the daily recommendation of 60 minutes/day. Previous studies have been centered only in physical activity markers, but the SB variables were not compared nor the segments of the school-recess with the out-of-school period or with the weekend. This study aimed to examine the intra- and inter-days differences in the objectively measured levels of PA and SB in adolescents. A sample of 156 Chilean school students (87 boys and 69 girls; M age=13.41; SD=.67 years) participated in the present study. Participants’ PA and SB were objectively measured by a GT3X accelerometer. Overall results showed that only 14% and 9% of Chilean adolescents achieved the daily recommendation of 60 minutes of MVPA on weekdays and the weekend, respectively. School recess was found the best moment for developing MVPA, followed by out-of-school time, and ending with weekend days presenting the worst scenario. Regarding the SB, Chilean adolescents were involved in SB 69.39% of the time on weekdays, and over 70% during the weekend. Different strategies are discussed in order to increase the MVPA and to decrease SB in each segment of a day.